What Happened to Antiracist Education? The 1993 Antiracism and Ethnocultural Equity Educational Reform in Ontario School Boards - Tateishi, Douglas (Université d'Ottawa / University of Ottawa, 2020)
This research uses an antiracism theoretical framework, arising from Stanley’s (2011, 2014) anti-essentialist antiracism and Dei’s (1996) anti-racism praxis, to focus on the four documents that comprised the Ontario Ministry of Education’s 1993 Antiracism and Ethnocultural Equity initiative (the initiative). The initiative required school boards to develop and implement policies to identify and eliminate racisms within their systems and schools. I used a methodology of constructivist grounded theory to trace the origins and content of the initiative through the lens of my 44-years of lived experience, during which I was a teacher, principal, superintendent, associate director of education, and ministry education officer. This thesis poses the overarching question: What happened to antiracism and ethnocultural equity? I find that although the initiative was a genuine antiracism project, it was destined to fail due to certain deficiencies. I conclude it had two critical deficiencies. First, it did not consider the four discrete cultures located in school boards (made up of supervisory officers, trustees, principals and teachers). Second, it did not provide these cultures with suitable pressures and supports to generate the individual and organizational changes envisioned. Finally I consider what the Ministry would need to do for such an antiracism reform to succeed? I argue systemic policy reform must be based on what I call strategic antiracist education. It would provide the members of the culture of supervisory officers with the necessary knowledge, authority, resources and supports, including professional development, to enable them to lead the members of the other school cultures in antiracist educational reform.
Keywords: Antiracist education; Educational policy